CAMPUR KODE DALAM LIRIK-LIRIK LAGU SAYKOJI - MOKODOMPIT, PEBRIAN FRANSISCO; LASUT, THERESIA M. C.; RANUNTU, GARRYN CH (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThis skripsi entitled ?Code Mixing in the Lyrics of Saykoji?s Songs: Sociolinguistic Analysis?. The aim of this research is to identify, analyze and describe the code mixing appeared in the lyrics of Saykoji?s songs. The theory that are used in this research is by Muysken (2000) and this research uses a descriptive method. The data was taken from Saykoji?s songs. The result of this research shows that there are three processes of code mixing in the lyrics of Saykoji?s songs through its insertion, alternation, and congruent lexicalization. Key Words: Sociolinguistic, Code Mixing, Internet, Saykoji?s Songs